Foundations of the social theory of Weber - Jawad, Hadeer Hassan; Al-Khalidi, Mohammed Abdullah (Al-Adab Journal, 2021)
From the emergence of sociology to the contemporary period, social theory has been subjected to conflict and an intellectual crisis within the field of social research; this led to the emergence of a group of thinkers who sought to arrive at an approach to keep pace with the changes and changes taking place in social reality. Max Weber (1864-1920 AD) is one of the most important Tibetans who dealt with sociology. In his study of sociology, Weber discussed several categories that helped define the features of social theory through which he sought to build an ideal model that serves the phenomenon or cause to be discussed. Among the most important of these sayings: understanding, meaning, causal interpretation, social action, ideal model, and finally social relationships.